A Black Educator in the Segregated South : Kentucky's Rufus B. Atwood - Smith, Gerald L., 1959- (Book collections on Project MUSE., 2015)
Black college presidents in the era of segregation walked a tightrope. They were expected to educate black youth without sufficient state and federal funding. Yet in the African American community they were supposed to represent power and influence and to be outspoken advocates of civil rights, despite the continual risk of offending the white politicians on whom they were dependent for funding. The dilemmas they faced in balancing these conflicting demands have never been fully examined. Gerald Smith's study of the long-time president of Kentucky State College helps fill that void. From 1929 t.